2016
DOI: 10.3174/ajnr.a4955
|View full text |Cite
|
Sign up to set email alerts
|

White Matter Injury and General Movements in High-Risk Preterm Infants

Abstract: BACKGROUND AND PURPOSE:Very preterm infants (birth weight, Ͻ1500 g) are at increased risk of cognitive and motor impairment, including cerebral palsy. These adverse neurodevelopmental outcomes are associated with white matter abnormalities on MR imaging at term-equivalent age. Cerebral palsy has been predicted by analysis of spontaneous movements in the infant termed "General Movement Assessment." The goal of this study was to determine the utility of General Movement Assessment in predicting adverse cognitive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
44
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(45 citation statements)
references
References 29 publications
0
44
1
Order By: Relevance
“…repetitive self-grooming and a reduction in social play behavior. In line with these findings, recent clinical studies revealed an association between diffuse WMI and motor abnormalities in preterm infants (Guo et al, 2017;Peyton et al, 2016Peyton et al, , 2017. Also, multiple studies have demonstrated that preterm infants are at risk to develop ASD later in life (Dudova et al, 2014;Johnson et al, 2010;Joseph et al, 2017;Kuzniewicz et al, 2014;Limperopoulos et al, 2008;Pritchard et al, 2016;Treyvaud et al, 2013).…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…repetitive self-grooming and a reduction in social play behavior. In line with these findings, recent clinical studies revealed an association between diffuse WMI and motor abnormalities in preterm infants (Guo et al, 2017;Peyton et al, 2016Peyton et al, , 2017. Also, multiple studies have demonstrated that preterm infants are at risk to develop ASD later in life (Dudova et al, 2014;Johnson et al, 2010;Joseph et al, 2017;Kuzniewicz et al, 2014;Limperopoulos et al, 2008;Pritchard et al, 2016;Treyvaud et al, 2013).…”
Section: Discussionmentioning
confidence: 84%
“…Additionally, activation of microglia and astrogliosis are important pathophysiological hallmarks of diffuse WMI (Buser et al, ; Haynes et al, ; Verney et al, ). Functionally, WMI is associated with behavioral, cognitive, motor and psychological problems, like autism spectrum disorders (ASD), later in life (Back & Miller, ; Dudova et al, ; Guo et al, ; Johnson, Hollis, Kochhar, Hennessy, Wolke, & Marlow, ; Joseph et al, ; Kuzniewicz et al, ; Limperopoulos et al, ; Peyton et al, ; Pritchard et al, ; Treyvaud et al, ). While antenatal administration of magnesium sulfate in women at risk for preterm delivery reduces the risk of cerebral palsy in the fetus (Crowther, Hiller, Doyle, & Haslam, ; Doyle, Crowther, Middleton, Marret, & Rouse, ; Gano et al, ; Rouse et al, ), limited treatment options are currently available to protect preterm infants against diffuse WMI.…”
Section: Introductionmentioning
confidence: 99%
“…Phenomenologically, assessment of infants' spontaneous behavior has recently gained a lot of interest for three reasons: First, it is well accepted that the highest ecological validity comes from studies performed in subject's native environment, i.e., the lab or hospital environment is at most sub-optimal for genuinely assessing neurodevelopmental performance. Second, the novel recording and analysis methodologies have made it possible to study subject's spontaneous activities in both lab and other environments [19,25] Third, both fundamental and applied research has shown that infant's spontaneous movements may provide an important global window to the infant brain function [7,17]. Besides bodily movements per se, spontaneous movements also support the development of higher cognitive functions through the organization of the action-perception-loop, gradually also enabling intentional exploration of the surrounding world.…”
Section: Introductionmentioning
confidence: 99%
“…Infant and Toddler Development -Third Edition (BSID-III) at 2 years of corrected age. 18 Studies focusing on very preterm children and the potential association between DTI metrics at term age and later motor development at school age are scarce. In this study, our aim was to assess whether DTI metrics at term age are associated with motor development at 11 years of age in very preterm children.…”
Section: Dti Metrics and Motor Outcomes Measured With The Bayley Scalmentioning
confidence: 99%
“…In these studies, the DTI metrics of the corpus callosum, posterior limb of the internal capsule and corticospinal tracts have been reported to associate with motor development . However, there is also one study reporting no associations between DTI metrics and motor outcomes measured with the Bayley Scales of Infant and Toddler Development – Third Edition (BSID‐III) at 2 years of corrected age …”
Section: Introductionmentioning
confidence: 99%